The missing link between high performance work practices and perceived organizational politics - Riaz, Adnan; Batool, Saima; Md Saad, Mohd Shamsuri (Fundacao Getulio Vargas, 2019)
A vast majority of research characterizes organizational politics as an aversive phenomenon and thus recommends exploring the factors that minimize its intensity. This study primarily endeavored to examine the role of high performance work practices (HPWPs) in controlling organizational politics. The moderating influence of Machiavellian personalities on HPWPs- politics was also evaluated. Through a questionnaire survey, 243 responses were obtained from engineers working in a local industrial area of capital city of Pakistan. The results showed an inverse relationship between HPWPs and perceived organizational politics (POP), and the moderating role of Machiavellianism was substantiated. Practical implications are presented based on the study results.